The Olympic games and cultural policy - Garcia, Beatriz (New York : Routledge, 2012)
"This book explores how cultural policies are reflected in the design, management and promotion of the Olympic Games. Garcia examines the concept and evolution of cultural policies throughout the recent history of the Olympic Games and then specifically evaluates the cultural program of the Sydney 2000 Olympic Games. She argues that the cultural relevance of a major event is highly dependent on the consistency of the policy choices informing its cultural dimensions, and demonstrates how such events frequently fail to leave long-term cultural legacies, and are often unable to provide an experience that fully engages and represents the host community, due to their over-emphasis on an economic rather than a social and cultural agenda"--
pt. I. Cultural policy and the Olympics movement -- pt. II. The Olympic games cultural programme : Olympic arts festivals in Sydney 2000 -- pt. III. Towards a culture-led Olympic games?
Includes bibliographical references and index.
Description based on metadata supplied by the publisher and other sources.
Electronic reproduction. Santa Fe, Arg.: elibro, 2020. Available via World Wide Web. Access may be limited to eLibro affiliated libraries.
Keywords: Olympics -- Social aspects; Olympics -- History; Electronic books